2017
DOI: 10.5114/aoms.2016.61938
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of exercise tolerance in cardiopulmonary testing with sustained safety after regular training in outpatients with systolic heart failure (NYHA III) and an implantable cardioverter-defibrillator. Prospective 18-month randomized study

Abstract: IntroductionThe aim of the study was to evaluate the impact of individual training on the level of physical capacity and echocardiographic parameters in patients with systolic heart failure (SHF), NYHA III and an implantable cardioverter-defibrillator (ICD).Material and methodsThe study included 84 patients with SHF, randomly assigned to one of two groups: with regular training (ICD-Ex) and a control group (ICD-control). The ICD-Ex group participated in a hospital rehabilitation program which after discharge w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Overall, in the absence of effective pharmacologic treatments available for patients with HFpEF, regular exercise training has shown strong objective evidence in improving quality of life and functional capacity for patients with HFpEF [ 31 , 32 ]. This study therefore sheds light on improved mortality over long-term follow-up with CRF in patients with HFpEF, which has not been sufficiently demonstrated in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the absence of effective pharmacologic treatments available for patients with HFpEF, regular exercise training has shown strong objective evidence in improving quality of life and functional capacity for patients with HFpEF [ 31 , 32 ]. This study therefore sheds light on improved mortality over long-term follow-up with CRF in patients with HFpEF, which has not been sufficiently demonstrated in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that the presence of a hospice medical director and standing orders may also contribute to the lower risk of readmission. Future randomized controlled trials need to examine whether these and other strategies such as improving physical activity and mobility incorporated into the home health services program would improve outcomes, thus providing evidence of cost effectiveness of a program that often allows hospitalized frail patients to go home [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPX) is a useful way to evaluate prognosis, risk of metabolic diseases, condition of diseases, determination of exercise intensity, and efficacy of exercise therapy [1][2][3][4][5] . The most popular marker is peak oxygen uptake (VO 2 ).…”
Section: Introductionmentioning
confidence: 99%